Proceedings of the 7th Annual Conference on Genetic and Evolutionary Computation 2005
DOI: 10.1145/1068009.1068207
|View full text |Cite
|
Sign up to set email alerts
|

On the complexity of hierarchical problem solving

Abstract: Competent Genetic Algorithms can efficiently address problems in which the linkage between variables is limited to a small order k. Problems with higher order dependencies can only be addressed efficiently if further problem properties exist that can be exploited. An important class of problems for which this occurs is that of hierarchical problems. Hierarchical problems can contain dependencies between all variables (k = n) while being solvable in polynomial time. An open question so far is what precise prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Recent results are along these lines [16] i.e., hierarchical model building . Additional refinements to the composition model have also been introduced [13]: (1) mutation for supporting population diversity (2) initial population limited to single (non-neutral) genes but allowed to incrementally increase, thus making the hierarchical gene linkage learning more explicit; and, (3) maintenance of a worst case tabu list of poorly performing genomes to bias against revisiting poor states during symbiosis.…”
Section: Symbiogenesis and Genetic Linkage Learningmentioning
confidence: 99%
“…Recent results are along these lines [16] i.e., hierarchical model building . Additional refinements to the composition model have also been introduced [13]: (1) mutation for supporting population diversity (2) initial population limited to single (non-neutral) genes but allowed to incrementally increase, thus making the hierarchical gene linkage learning more explicit; and, (3) maintenance of a worst case tabu list of poorly performing genomes to bias against revisiting poor states during symbiosis.…”
Section: Symbiogenesis and Genetic Linkage Learningmentioning
confidence: 99%
“…As stated by de Jong, Watson, and Thierens (2005), 'two variables in a problem are interdependent if the fitness contribution or optimal setting for one variable depends on the setting of the other variable', and such relationship between variables is often referred to as linkage in the GA literature. In order to obtain the full linkage information of a pair of variables, the fitness contribution or optimal setting of these two variables will be examined on all possible settings of the other variables.…”
Section: Linkage and Bbsmentioning
confidence: 99%
“…Prior models have been suggested that investigate the evolution of symbiogenic encapsulation [10][11][12], or abstractions thereof [13]. These models use a variety of mechanisms to determine the suitability of symbiogenic joins, including Pareto dominance [10], context-optimality [13], and maximising reciprocal synergy [12].…”
Section: Introductionmentioning
confidence: 99%
“…These models use a variety of mechanisms to determine the suitability of symbiogenic joins, including Pareto dominance [10], context-optimality [13], and maximising reciprocal synergy [12]. In [14] the evolution of 'observers' provides groupings to coarsegrain an adaptive landscape.…”
Section: Introductionmentioning
confidence: 99%